Strategi Manajemen Kepemimpinan Kepala Sekolah dalam Meningkatkan Kualitas Kinerja Pendidik dan Tenaga Kependidikan - Muflikha Muflikha; Budi Haryanto (PALAPA, 2019)
This paper aims to analyze the Principal's leadership management strategy in improving the Performance of Educators and Education Personnel. The Headmaster Leadership management strategy is one of the keys to success for improving the quality of performance of educators and education personnel. Increasing the quality of the performance of educators and education personnel will have a significant impact on the educational process and the achievement of desired educational goals. This paper uses a descriptive qualitative approach that seeks to describe the form of leadership management strategies for school principals in order to improve the quality of educational performance and education personnel. The results of this study indicate that (1) the Principal's management strategy has a very important role in improving the performance of educators and education personnel. (2) the quality of the performance of educators and education personnel has an impact on improving the quality of learning and achieving educational goals to the fullest.